Farmer uncertainty and demand for rice varietal identity information: DNA fingerprinting of smallholder rice varieties in Côte d’Ivoire - Tyack, N.; Arouna, Aminou; Amoah, N.; Aboudou, R. (2023)
Information asymmetry is a key challenge facing farmers in sub-Saharan Africa, particularly regarding the identity and quality of crop varieties and other agricultural inputs. In this research, we contribute to a recent economics literature that uses advances in DNA fingerprinting technology and affordability to directly measure the identity of crop varieties, allowing this variable to be compared with farmers’ beliefs about the varieties that they cultivate. In our study, we additionally utilize a novel approach in which we elicit the demand of rice farmers in central Côte d’Ivoire for information about the variety they cultivate as well as their own beliefs about how sure they are of the variety’s identity. We connect our DNA fingerprinting analysis of producer seed samples to survey questions related to producer beliefs and demand, and find that the majority of the farmers in our dataset are not certain about the identity of the variety they cultivate. We further find that around 98 percent of producers in our dataset are willing to pay to obtain the results of DNA fingerprinting analysis of the variety they currently cultivate, from a minimum of around $0.20 to a maximum of ~$36 USD.